Perancangan Enterprise Architecture Menggunakan Togaf Adm pada SMP Nurul Falah Pekanbaru - Muhammad Iqbal Indrawan; Febi Nur Salisah; Idria Maita; Fitriani Muttakin; Eki Saputra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
SMP Nurul Falah is one of the private junior high schools under the auspices of the Nurul Falah foundation. This school was founded in 1974. However, for now, SMP Nurul Falah has not been able to utilize IT/IS optimally. The input and processing of data at SMP Nurul Falah is still manual, which is still using Microsoft Office as processing and inputting data and there is no integrated information system between one field and another which causes data input to take a long time and in the use and exchange of data it is still not possible to do. Therefore we need an information system architecture design modeling, the modeling is Togaf Adm which consists of preliminary stages, architecture vision, architecture bussines, information system architecture, architecture technology, opportunities & solutions, migration planning, implementation governance, and architecture change management. The result of this research is togaf adm design which focuses on the preliminary phase and vision architecture that can be used to design and develop information systems.